Virtual Reality-Based Islamic Religious Education: Enhancing Students’ Religious Experience and Historical Understanding - Mowafg Masuwd; Markhabat Bolat; Mohammad Ahmad Bani Amer (Ar-rayyan: Journal Of Islamic Education, 2026)
Immersive technologies such as Virtual Reality (VR) have transformed educational practices by creating interactive and experiential learning environments. Nevertheless, their implementation in Islamic Religious Education remains relatively unexplored. This study aims to investigate the effectiveness of VR-based instruction in improving students’ understanding of Islamic history and enhancing meaningful religious learning experiences. A quasi-experimental design involving 186 secondary school students was employed. Students in the experimental group participated in VR-assisted learning activities featuring virtual tours of Islamic historical sites, simulations of Hajj rituals, and immersive explorations of Islamic civilization, while the control group received conventional instruction. Data were collected through achievement tests, motivation questionnaires, classroom observations, and interviews. The results indicate that VR significantly improves conceptual understanding, historical awareness, student engagement, and learning motivation. Students also reported greater emotional involvement and stronger connections with Islamic historical narratives. The novelty of this study is the development of an Immersive Islamic Learning Model that integrates virtual reality technology with experiential learning principles to strengthen cognitive, affective, and spiritual dimensions of Islamic Religious Education